Measurement of the cross-section ratio σψ(2S)/σJ/ψ(1S) in exclusive photoproduction at HERA - Abt, Iris; Adamus, M.; Aggarwal, R.; Aushev, V.; Behnke, O.; Bertolin, A.; Bloch, I.; Brock, I.; Brook, N. H.; Brugnera, R.; Bruni, A.; Bussey, P. J.; et al. (Journal of high energy physics, 2022)
The exclusive photoproduction reactions γp → J/ψ(1S)p and γp → ψ(2S)p have been measured at an ep centre-of-mass energy of 318 GeV with the ZEUS detector at HERA using an integrated luminosity of 373 pb−1. The measurement was made in the kinematic range 30 < W < 180 GeV, Q2 < 1 GeV2 and |t| < 1 GeV2, where W is the photon-proton centre-of-mass energy, Q2 is the photon virtuality and t is the squared four-momentum transfer at the proton vertex. The decay channels used were J/ψ(1S) → μ+μ−, ψ(2S) → μ+μ− and ψ(2S) → J/ψ(1S)π+π− with subsequent decay J/ψ(1S) → μ+μ−. The ratio of the production cross sections, R = σψ(2S)/σJ/ψ(1S), has been measured as a function of W and |t| and compared to previous data in photoproduction and deep inelastic scattering and with predictions of QCD-inspired models of exclusive vector-meson production, which are in reasonable agreement with the data.
Im Titel sind die Formulierungen "psi(2S)" und "J/psi(1S)" tiefgestellt
The ZEUS collaboration: I. Abt, M. Adamus, R. Aggarwal, V. Aushev, O. Behnke, A. Bertolin, I. Bloch, I. Brock, N.H. Brook, R. Brugnera, A. Bruni, P.J. Bussey, A. Caldwell, C.D. Catterall, J. Chwastowski, J. Ciborowski, R. Ciesielski, A.M. Cooper-Sarkar, M. Corradi, R.K. Dementiev, S. Dusini, J. Ferrando, B. Foster, E. Gallo, D. Gangadharan, A. Garfagnini, A. Geiser, G. Grzelak, C. Gwenlan, D. Hochman, N.Z. Jomhari, I. Kadenko, U. Karshon, P. Kaur, R. Klanner, U. Klein, I.A. Korzhavina, N. Kovalchuk, M. Kuze, B.B. Levchenko, A. Levy, B. Löhr, E. Lohrmann, A. Longhin, F. Lorkowski, I. Makarenko, J. Malka, S. Masciocchi, K. Nagano, J.D. Nam, Yu. Onishchuk, E. Paul, I. Pidhurskyi, A. Polini, M. Przybycień, A. Quintero, I. Rubinsky, M. Ruspa, U. Schneekloth, T. Schörner-Sadenius, I. Selyuzhenkov, M. Shchedrolosiev, L.M. Shcheglova, I.O. Skillicorn, W. Słomiński, A. Solano, L. Stanco, N. Stefaniuk, B. Surrow, K. Tokushuku, J. Tomaszewska, A. Trofymov, O. Turkot, T. Tymieniecka, A. Verbytskyi, W.A.T. Wan Abdullah, K. Wichmann, M. Wing, S. Yamada, Y. Yamazaki, A.F. Żarnecki, O. Zenaiev
Gesehen am 26.04.2023